Expression of MRF4, a myogenic helix-loop-helix protein, produces multiple changes in the myogenic program of BC3H-1 cells. - Block, N E (1992)
Expression of MRF4, a myogenic regulatory factor of the basic helix-loop-helix type, produced multiple changes in the myogenic program of the BC3H-1 cell line. BC3H-1 cells that stably expressed exogenous MRF4 were prepared and termed BR cell lines. Upon differentiation, the BR cells were found to have three muscle-specific properties (endogenous MyoD expression, myoblast fusion, and fast myosin light-chain 1 expression) that the parent BC3H-1 cells did not have. Of the four known myogenic regulatory factors (MyoD, myogenin, Myf-5, and MRF4), only MRF4 was capable of activating expression of the endogenous BC3H-1 myoD gene. In addition, the pattern of Myf-5 expression in BR cells was the opposite of that in BC3H-1 cells. Myf-5 expression was low in BR myoblasts and showed a small increase upon myotube formation, whereas Myf-5 expression was high in BC3H-1 myoblasts and decreased upon differentiation. Though the MRF4-transfected BR cells fused to form large myotubes and expressed fast myosin light-chain 1, the pattern of myosin heavy-chain isoform expression was the same in the BR and the nonfusing parent BC3H-1 cells, suggesting that factors in addition to the MyoD family members regulate myosin heavy-chain isoform expression patterns in BC3H-1 cells. In contrast to the changes produced by MRF4 expression, overexpression of Myf-5 did not alter BC3H-1 myogenesis. The results suggest that differential expression of the myogenic regulatory factors of the MyoD family may be one mechanism for generating cells with diverse myogenic phenotypes.